The Relationship between Secondary Structure and Biodegradation Behavior of Silk Fibroin Scaffolds - Yongpei Hu (Advances in Materials Science and Engineering, 2012)
Silk fibroin has a unique and useful combination of properties, including good biocompatibility and excellent mechanical performance. These features provided early clues to the utility of regenerated silk fibroin as a scaffold/matrix for tissue engineering. The silk fibroin scaffolds used for tissue engineering should degrade at a rate that matches the tissue growth rate. The relationship between secondary structure and biodegradation behavior of silk fibroin scaffolds was investigated in this study. Scaffolds with different secondary structure were prepared by controlling the freezing temperature and by treatment with carbodiimide or ethanol. The quantitative proportions of each secondary structure were obtained by Fourier transform infrared spectroscopy (FTIR), and each sample was then degraded in vitro with collagenase IA for 18 days. The results show that a high content of β-sheet structure leads to a low degradation rate. The random coil region in the silk fibroin material is degraded, whereas the crystal region remains stable and the amount of β-sheet structure increases during incubation. The results demonstrate that it is possible to control the degradation rate of a silk fibroin scaffold by controlling the content of β-sheet structure.